2005
DOI: 10.1111/j.1468-3083.2005.01094.x
|View full text |Cite
|
Sign up to set email alerts
|

Immunophenotypic analysis of the p53 gene in non‐melanoma skin cancer and correlation with apoptosis and cell proliferation

Abstract: p53 immunoreactivity was high in the majority of the skin carcinomas examined and correlated positively with cell proliferation and negatively with apoptosis. The p53 protein overexpression appears to be related to an inactivated protein resulting from mutations of the p53 gene or other unclear molecular mechanisms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
33
1
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(42 citation statements)
references
References 29 publications
(60 reference statements)
5
33
1
2
Order By: Relevance
“…The Ki-67 antigen, a high molecular weight non-histone protein, is generally accepted to be a reliable marker of many types of proliferating cells [15] [16]. It is a nuclear structure expressed during all phases of the cell cycle (G 1 , S, G 2 and mitosis) but not by cells that are failing to undergo division.…”
Section: Discussionmentioning
confidence: 99%
“…The Ki-67 antigen, a high molecular weight non-histone protein, is generally accepted to be a reliable marker of many types of proliferating cells [15] [16]. It is a nuclear structure expressed during all phases of the cell cycle (G 1 , S, G 2 and mitosis) but not by cells that are failing to undergo division.…”
Section: Discussionmentioning
confidence: 99%
“…The p53 protein detected through immunohistochemical staining represents stabilized and probably mostly mutant rather than wild-type p53 protein [38]. This is because wild-type protein has a very short half-life (5–20 min) and is not readily detectable by immunohistochemistry, while the mutated p53 gene encodes a protein with a substantially longer half-life (5–24 h) as indicated by p53 immunoreactivity [39,40,41]. Other authors [6] however have found no association between p53 expression in the epidermis and clinically assessed photoaging, which may be partly explained by a cruder system used in evaluating photoaging, and as acknowledged by the authors, by their exclusion of more severe clinical photoaging levels.…”
Section: Discussionmentioning
confidence: 99%
“…The p53 tumor-suppressor gene is the classic example of these genes, as it is found mutated in 50-90% of human malignant tumors including skin cancers. [42327] The tumor-suppressor gene p53, located on the short arm of chromosome 17 (17p13.1), encodes for a nuclear protein which regulates cell proliferation by inhibiting cells entering S-phase. The p53 mutations are alleged to be the commonest genetic abnormality in human cancer.…”
Section: Discussionmentioning
confidence: 99%